Comparability and validity of cancer registry data in the northwest of Russia. (3rd October 2021) - Barchuk, Anton; Tursun-zade, Rustam; Belayev, Alexey; Moore, Malcolm; Komarov, Yuri; Moshina, Nataliia; Anttila, Ahti; Nevalainen, Jaakko; Auvinen, Anssi; Ryzhov, Anton; Znaor, Ariana
Abstract: Background: Despite the elaborate history of statistical reporting in the USSR, Russia established modern population-based cancer registries (PBCR) only in the 1990s. The quality of PBCRs data has not been thoroughly analyzed. This study aims at assessing the comparability and validity of cancer statistics in regions of the Northwestern Federal District (NWFD) of Russia. Material and methods: Data from ten Russian regional PBCRs covering ∼13 million (∼5 million in St. Petersburg) were processed in line with IARC/IACR and ENCR recommendations. We extracted and analyzed all registered cases but focused on cases diagnosed between 2008 and 2017. For comparability and validity assessment, we applied established qualitative and quantitative methods. Results: Data collection in NWFD is in line with international standards. Distributions of diagnosis dates revealed higher variation in several regions, but overall, distributions are relatively uniform. The proportion of multiple primaries between 2008 and 2017 ranged from 6.7% in Vologda Oblast to 12.4% in Saint-Petersburg. We observed substantial regional heterogeneity for most indicators of validity. In 2013–2017, proportions of morphologically verified cases ranged between 61.7 and 89%. Death certificates only (DCO) cases proportion was in the range of 1–14% for all regions, except for Saint-Petersburg (up to 23%). The proportion of cases with a primary site unknown was between 1 and 3%. Certain cancer types (e.g., pancreas, liver, hematological malignancies, and CNS tumors) and cancers in older age groups showed lower validity. Conclusion: While the overall level of comparability and validity of PBCRs data of four out of ten regions of NWFD of Russia meets the international standards, differences between the regions are substantial. The local instructions for cancer registration need to be updated and implemented. The data validity assessment also reflects pitfalls in the quality of diagnosis of certain cancer types and patient groups.